Are stricter investment rules contagious? Host country competition for foreign direct investment through international agreements - Eric Neumayer; Peter Nunnenkamp; Martin Roy (Kiel Institute for the World Economy (IfW), 2014)
We argue that the trend toward international investment agreements (IIAs) with stricter investment rules is driven by competitive diffusion, namely defensive moves of developing countries concerned about foreign direct investment (FDI) diversion in favor of competing host countries. Accounting for spatial dependence in the formation of bilateral investment treaties (BITs) and preferential trade agreements (PTAs) that contain investment provisions, we find that the increase in agreements with stricter provisions on investor-state dispute settlement and pre-establishment national treatment is a contagious process. Specifically, a developing country is more likely to sign an agreement with weak investment provisions if other developing countries that compete for FDI from the same developed country have previously signed agreements with similarly weak provisions. Conversely, contagion in agreements with strong provisions exclusively derives from agreements with strong provisions that other FDI-competing developing countries have previously signed with a specific developed source country of FDI.
Keywords: F21; F53; 330; bilateral investment treaties; preferential trade agreements; investment provisions; competition for FDI; spatial dependence